Waiting for jobs - Radhicka Kapoor (Indian Council for Research on International Economic Relations (ICRIER), 2017)
Employment data in India is far from adequate if policy responses have to be more effective and timely. Most employment surveys suffer from drawbacks such as limited data coverage, infrequent data collection and long time lags. To address these gaps and revamp the existing employment data systems, the government has put in place a Task Force. However, new employment data is unlikely to be available until the latter half of next year. Understanding and analyzing employment trends in the interim period is imperative. This study attempts to do so by undertaking a detailed analysis of multiple data sources-households' employment and unemployment surveys, enterprise surveys, administrative datasets, data from government schemes and National Accounts Statistics. Results from our analysis reflect a sluggish pace of job creation over the last three years and underscore the severity of India's jobs crisis. However, it needs to be noted that simply creating a large number of jobs in the face of intensifying demographic pressures is inadequate. These jobs need to be "productive jobs".
Keywords: J21; J29; J40; J46; J60; 330; Labour Force; Employment; Employment Data; Household Surveys; Enterprise Surveys